Body Surface Mapping of Ventricular Repolarization Heterogeneity: An Ex-vivo Multiparameter Study - Meo, Marianna; Bonizzi, Pietro; Bear, Laura R.; Cluitmans, Matthijs; Abell, Emma; Haïssaguerre, Michel; Bernus, Olivier; Dubois, Rémi (Frontiers in Physiology, 2020)
Background Increased heterogeneity of ventricular repolarization is associated with life-threatening arrhythmia and sudden cardiac death. T-wave analysis through body surface potential mapping (BSPM) is a promising tool for risk stratification, but the clinical effectiveness of current electrocardiographic indices is still unclear, with limited experimental validation. This study aims to investigate performance of noninvasive state-of-the-art and novel T-wave markers for repolarization dispersion in an ex-vivo model. Methods Langendorff-perfused pig hearts (N=7) were suspended in a human-shaped 256-electrode torso tank. Tank potentials were recorded during sinus rhythm before and after introducing repolarization inhomogeneities through local perfusion with dofetilide and/or pinacidil. Drug-induced repolarization gradients were investigated from BSPMs at different experiment phases. Dispersion of electrical recovery was quantified by duration parameters, i.e. the time interval between the peak and the offset of T-wave (TPEAK-TEND) and QT interval, and variability over time and electrodes was also assessed. The degree of T-wave symmetry to the peak was quantified by the ratio between the terminal and initial portions of T-wave area (Asy). Morphological variability between left and right BSPM electrodes was measured by dynamic time warping (DTW). Finally, T-wave organization was assessed by the complexity of repolarization index (CR), i.e., the amount of energy non-preserved by the dominant eigenvector computed by principal component analysis (PCA), and the error between each multilead T-wave and its 3D PCA approximation (NMSE). Body surface indices were compared with global measures of epicardial dispersion of repolarization, and with local gradients between adjacent ventricular sites. Results After drug intervention, both regional and global repolarization heterogeneity were significantly enhanced. On the body surface, TPEAK-TEND was significantly prolonged and less stable in time in all experiments, while QT interval showed higher variability across the interventions in terms of duration and spatial dispersion. The rising slope of the repolarization profile was steeper, and T-waves were more asymmetric than at baseline. Interventricular shape dissimilarity was enhanced by repolarization gradients according to DTW. Organized T-wave patterns were associated with abnormal repolarization, and they were properly described by the first principal components. Conclusions Repolarization heterogeneity significantly affects T-wave properties, and can be noninvasively captured by BSPM-based metrics.